Bullying and victimization among adolescents in Tuva: prevalence, structure, age and gender differences - Evert, Lidiya S. (The New Research of Tuva, 2026)
This article examines bullying and victimization among adolescents in the Republic of Tuva, focusing on their prevalence and structure by age and gender. The analysis is based on the results of a large-scale screening study of random samples of adolescents in the Republic of Tuva (n = 1,366), conducted online in 2022–2023 using Google Forms and the ROSA psychometric questionnaire (A. Sourander, 2012) to determine the presence or absence of bullying—traditional bullying, cyberbullying, or a combination of the two. The frequency, types, methods, and manifestations of bullying and cyberbullying were analyzed across age and gender groups. The frequency of bullying episodes was examined separately for each type of bullying, taking into account the participant’s role in the bullying process (victim, aggressor). The forms of traditional and cyberbullying, the profiles of aggressors, and information on the probable causes of bullying and the victim’s attempts to seek help are described. Among Tuvan adolescents, boys were significantly more likely to be involved in bullying than girls. In traditional bullying, Tuvan boys were more likely than their female peers to be victims (14.6% versus 8.0% for girls), aggressors (13.9% versus 5.5%), and victim–aggressors (11.3% versus 3.4%). The distribution of these characteristics was similar for cyberbullying and combined bullying: Tuvan boys demonstrated higher rates on all of these indicators than Tuvan girls.